The Efficacy and Neural Correlates of ERP-based Therapy for OCD & TS: A Systematic Review and Meta-Analysis - Junjuan Yan; Linyu Cui; Mengyu Wang; Yonghua Cui; Ying Li (Journal of Integrative Neuroscience, 2022)
Background: Exposure and response prevention (ERP) is a form of cognitive behavioral therapy that can effectively relieve obsessive-compulsive symptoms and tic symptoms in patients with obsessive-compulsive disorder (OCD) and Tourette syndrome (TS). However, the effect size of ERP-based therapy is still unclear. Methods: In this study, we performed a meta-analysis to identify the efficacy of ERP-based therapy for individuals with OCD and TS. The standard mean difference (SMD) with a 95% confidence interval (CI) was calculated to assess the effect size of the efficacy for ERP-based therapy. We used subgroup and meta-regression analyses to explore the heterogeneity of the pooled SMD of ERP-based therapy for OCD. We also summarized the neuroimaging studies for ERP-based therapy for OCD. This meta-analysis was registered within the International Platform of Registered Systematic Review and Meta-analysis Protocols (number: INPLASY2021120112). Results: A total of 18 studies including a total of 1057 patients with OCD and 3 studies including 267 with TS/chronic tic disorder were identified. We did not observe any indication of publication bias using Egger’s funnel plot (p = 0.41). We observed a small-to-medium effect size of ERP for both OCD (SMD = –0.27, 95% CI: –0.53 to –0.01) and TS/chronic tic disorder (SMD = –0.35, 95% CI: –0.59 to –0.1). We found no heterogeneity of ERP-based therapy for OCD between the ERP-based therapy subgroup and medicine subgroup in the subgroup analysis (p = 0.72). We found no heterogeneity of ERP-based therapy for OCD between the child subgroup and adult subgroup in the subgroup analysis (p = 0.37). We used meta-regression analysis to identify the heterogeneity of ERP-based therapy for OCD and found that the sessions of therapy and publication year did not account for any significant heterogeneity (p > 0.05). The neurological mechanism of EPR-based therapy is unclear, but it may lie in changes in the prefrontal cortex and anterior cingulate cortex. Conclusions: In conclusion, we found that ERP-based therapy is effective for patients with OCD and TS/chronic tic disorder. We suggest a combination with other therapies and the development of online ERP services that might prove a promising new direction for healthcare providers.